2014
DOI: 10.1093/mnras/stu028
|View full text |Cite
|
Sign up to set email alerts
|

Dust from asymptotic giant branch stars: relevant factors and modelling uncertainties

Abstract: The dust formation process in the winds of Asymptotic Giant Branch stars is discussed, based on full evolutionary models of stars with mass in the range 1M ⊙ M 8M ⊙ , and metallicities 0.001 < Z < 0.008. Dust grains are assumed to form in an isotropically expanding wind, by growth of pre-existing seed nuclei.Convection, for what concerns the treatment of convective borders and the efficiency of the schematization adopted, turns out to be the physical ingredient used to calculate the evolutionary sequences with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(184 citation statements)
references
References 66 publications
5
179
0
Order By: Relevance
“…All the relevant equations, with a detailed explanation of the physical assumptions adopted, can be found in Ferrarotti & Gail (2006) and in the series of papers on this argument published by our group (Ventura et al 2012a,b;Di Criscienzo et al 2013;Ventura et al 2014a). …”
Section: Dust Formation In the Winds Of Agb Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the relevant equations, with a detailed explanation of the physical assumptions adopted, can be found in Ferrarotti & Gail (2006) and in the series of papers on this argument published by our group (Ventura et al 2012a,b;Di Criscienzo et al 2013;Ventura et al 2014a). …”
Section: Dust Formation In the Winds Of Agb Starsmentioning
confidence: 99%
“…The need for some extra-mixing was invoked by Herwig et al (2007), based on numerical simulations and, more recently, by Kamath et al (2012), on the basis of the comparison between the observed and expected transition luminosity from O-rich to C-rich stars in clusters in the MC. Extra-mixing from the bottom of the envelope has been used in almost the totality of the most recent works on AGB modelling (Cristallo et al 2009;Weiss & Ferguson 2009;Ventura et al 2014a;García-Hernández et al 2016).…”
Section: Pne In the Smc: A Further Test For Agb Modellingmentioning
confidence: 99%
“…We consider that Fig. 4 but showing the predictions of stellar evolution models for Z = 0.001 (green squares) by Ventura et al (2013Ventura et al ( , 2014b and Z = 0.004 (red triangles) by Ventura et al (2014a, V14). See text for discussion.…”
Section: Testing Other Stellar Evolution Modelsmentioning
confidence: 99%
“…8 and 9 we explore the behaviour of 12 + log (N/H) vs. 12 + log (He/H) and log (N/O), and 12 + log (Ne/H) vs. 12 + log (O/H) with models by Ventura et al (2013Ventura et al ( , 2014b Ventura et al (2013Ventura et al ( , 2014b and Z = 0.004 (red triangles) by Ventura et al (2014a, V14). See text for discussion.…”
Section: Testing Other Stellar Evolution Modelsmentioning
confidence: 99%
“…these stars. Ventura et al [23][24], Di Criscienzo et al [25], and Ventura et al [26] have computed the composition and grain size distributions of dust produced by stars with masses 0.8 < M * < 8 M at different metallicities (3 × 10 −4 < Z < 8 × 10 −3 ). By starting from these results, to improve the presented analysis, it would be useful to compute the extinction curve of AGB and super AGB stars.…”
Section: Discussionmentioning
confidence: 99%